Ohranjanje živosti ženskospolskih priponskih obrazil v sodobni zgodovini slovenskega jezika - Voršič, Ines (Studia Historica Slovenica, 2017)
The paper deals with the productivity of feminine suffixes in the recent history of the Slovene language. It focuses on the period at the turn of the new millennium, a period of great absorption of new words into the Slovene language. The paper raises the question if these new words have also brought changes into the Slovene word-formational system, and illustrates it with the example of feminine suffixes. The study looks at productive suffixes for the derivation of feminine words which were formed in the time of the transition from the 20th to the 21st centuries and compares them with the overview of feminine suffixes based on words recorded until the 1990s.
Keywords: slovenščina; slovnični spol; zgodovinsko jezikoslovje